Biogas Production from Tofu Liquid Waste with Cow Manure Mixture - Yudhi Sudarto; Salundik Salundik; Moch. Sriduresta Soenarno (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Biogas is a mixture of several gases produced from the process of overhauling organic materials by microorganisms in a state without air or anaerobically. This study aims to analyze the production and quality of biogas produced from tofu liquid waste with a mixture of cow dung. The study was conducted with 4 treatments, namely 80% liquid waste tofu and water + 20% cow dung (T80K20), 70% liquid waste tofu and water + 70% cow dung (T70K30), 60% liquid waste tofu and water + 40% dung cattle (T60K40), and 50% tofu liquid waste and water + 50% cow dung (T50K50). Each was replicated 3 times with data analysis using a completely randomized design (CRD). The highest methane gas production in the T50K50 treatment was 64,986.97 ml and the highest methane gas content in the T50K50 treatment was 43% in the sixth week.   Keywords:Anaerob,Carbon dioxide,Methane,Gas production.